2017
DOI: 10.1038/ncomms14042
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries portfolio diversification and turnover buffer Alaskan fishing communities from abrupt resource and market changes

Abstract: Abrupt shifts in natural resources and their markets are a ubiquitous challenge to human communities. Building resilient social-ecological systems requires approaches that are robust to uncertainty and to regime shifts. Harvesting diverse portfolios of natural resources and adapting portfolios in response to change could stabilize economies reliant on natural resources and their markets, both of which are prone to unpredictable shifts. Here we use fisheries catch and revenue data from Alaskan fishing communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 36 publications
(53 reference statements)
2
110
0
1
Order By: Relevance
“…Our models focused on species diversity as a possible predictor of revenue and revenue variability while controlling for effort. For consistency with previous analyses (10,13,14,29,35,43), we calculated effective species diversity for permit holder i and time (year) t as the inverse of Simpson's concentration index λ (21,22) [this index is also referred to in economics as the Herfindahl-Hirschman Index (44)] weighted by revenue R:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our models focused on species diversity as a possible predictor of revenue and revenue variability while controlling for effort. For consistency with previous analyses (10,13,14,29,35,43), we calculated effective species diversity for permit holder i and time (year) t as the inverse of Simpson's concentration index λ (21,22) [this index is also referred to in economics as the Herfindahl-Hirschman Index (44)] weighted by revenue R:…”
Section: Methodsmentioning
confidence: 99%
“…The most effective option to reduce revenue variability via diversification-purchasing additional permits-is also expensive, often limited by regulations, and therefore unavailable to many. the majority of research examining the effects of diversification on revenue does so at aggregate levels that combine individuals [e.g., counties or communities (10,13,14)]. Thus, key uncertainties remain about the relationship among diversity, fishing revenue, and fishing revenue variability at the level of the individual.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Sethi et al (11) found that Alaskan communities with larger and/or more diverse fishing portfolios experienced lower variability of fishing revenues. Cline et al (12) found that Alaskan fishing communities with more diversified fishing portfolios were able to maintain or increase fishing revenues in the face of major long-term regime shifts, while those with less diversified portfolios suffered declines in revenues, suggesting that diversification may be a good hedge against climate change-driven shifts in fisheries productivity.…”
mentioning
confidence: 99%
“…Commercial capture fisheries are especially vulnerable to abrupt environmental perturbations and unexpected shifts in market conditions (Anderson et al., ; Cline, Schindler, & Hilborn, ; Holland et al., ). There is a critical need to explore resilient management strategies that are robust to uncertainties and regime shifts in fisheries resources and markets.…”
Section: Introductionmentioning
confidence: 99%